Field investigation and rockfall hazard zonation at the Shijing Mountains Sutra caves cultural heritage (China) - Wang, Xueliang; Zhang, Luqing; Wang, Sijing; Agliardi, Federico; Frattini, Paolo; Crosta, Giovanni B; Yang, Zhifa (Environmental earth sciences, 2012)
Sutra inscriptions have been a main means for Buddhistic monks to pass on their teachings. Nine Sutra caves used to store about 5,000 Pleromas carved during the Sui Dynasty of China, more than 1,000 years ago, were found in the Shijing Mountains close to Beijing. These Sutra caves area have been affected by past failures and are subject to serious potential rockfall hazard from the relatively low rocky cliffs where caves are located. The aim of this study was a preliminary assessment of rockfall hazard for this cultural heritage site to support the design of safe tourist paths. The slope geometry has been surveyed by means of a laser profiler. These slope profiles have been used for two-dimensional distinct elements and rockfall simulations. The volumes of more probably unstable rock blocks were measured in situ. The results show that the runout distance ranges between 1.6 and 12.5 m affecting the most important tour route. The rockfalls threaten the life safety of tourists walking around and waiting for visiting the Sutra caves. Based on the analysis mentioned above, a zonation map of runout distance was accomplished. In the map, the range between the release points of the potential rockfalls and the minimum runout distance is defined as the most dangerous zone. The range between the maximum and the minimum runout distance is defined as danger zone. The range beyond the runout distance is defined as a safe zone. The map provides the guidance to the selection of safe tour routes at the scenic site. Finally, to reduce the rockfall hazard, remedial measures including rock bolts, placement of an absorbing layer of loose material and flexible barriers are suggested.